2018
DOI: 10.1159/000488069
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Polymorphisms in Patients with IgA Nephropathy Correlate with Proteinuria

Abstract: Background/Aims: IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis and still constitutes one of the most important causes of end-stage renal disease. Abnormal T cell responses may play a role in IgAN pathogenesis. Co-stimulatory molecules such as cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) are important for naive T cells to initiate and terminate immune responses. Single nucleotide polymorphisms (SNPs) in the CTLA4 gene locus are associated with several autoimmune diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
1
4
0
1
Order By: Relevance
“…However, some studies reported the contrary results [39]. Another factor affecting the function of Tregs in IgAN is an expression of CTLA-4; Jacob et al reported that polymorphisms attributed to decreased CTLA-4 gene expression were associated with higher proteinuria in IgAN patients [40]. However, the actual Treg’s CTLA-4 protein level was not investigated.…”
Section: Alterations Of T Cell Subpopulations In Iga Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies reported the contrary results [39]. Another factor affecting the function of Tregs in IgAN is an expression of CTLA-4; Jacob et al reported that polymorphisms attributed to decreased CTLA-4 gene expression were associated with higher proteinuria in IgAN patients [40]. However, the actual Treg’s CTLA-4 protein level was not investigated.…”
Section: Alterations Of T Cell Subpopulations In Iga Nephropathymentioning
confidence: 99%
“…Proteinuria-positive patients have a higher frequency of Th22 cells than proteinuria-negative IgAN patients and healthy people [14]. Moreover, higher proteinuria was observed in the patients possessing polymorphisms that caused a decreased expression of CTLA-4, immunosuppressive protein expressed on Tregs [40]. On the other hand, negative correlations were observed between the severity of 24-h proteinuria and tonsillar Th1/Th2 ratio [21], miR-155 level in PBMC [15], and frequency of activated Tregs [13].…”
Section: Clinical Correlations With T Cell Alterationsmentioning
confidence: 99%
“…The CTLA-4 rs231726 gene is associated with a higher risk of developing IgA nephropathy (Wang et al 2014), and the CTLA-4 rs231779 gene is associated with proteinuria, podocyte foot process effacement, and advanced mesangial proliferation (Kim et al 2011). Additionally, data obtained by Jacob et al (2018) support the hypothesis that CTLA-4 may be involved in the development and progression of IgA nephropathy. They found that frequencies of the –318/C/T SNP within the CTLA-4 gene locus appreciably differ between IgA nephropathy patients and healthy controls.…”
Section: Discussionmentioning
confidence: 68%
“…CTLA4 is a negative regulator in CD28 signaling and plays a key role in the initiation and termination of immune responses, whereas ICOS regulates the activation and tolerance of T cells. The G allele in CTLA4 rs231779 significantly increased the risk and was related to the prevalence of proteinuria ( 15 , 56 ). As for the correlation between SNPs and clinical symptoms, HLA-DQB1/DRB1 had a high association with a minor allele in rs2856717 that cannot be covered by adjustment of LD structure, protective haplotype (ACAT) and at-risk haplotypes (ATAT, GCGT).…”
Section: Discussionmentioning
confidence: 99%